The variation of the monodromy group in families of stratified bundles in positive characteristic - Battiston, Giulia (Documenta mathematica, 2015)
In this article we study smooth families of stratified bundles in positive characteristic and the variation of their monodromy group. Our aim is, in particular, to strengthen the weak form of the positive equicharacteristic p-curvature conjecture stated and proved by Esnault and Langer.